DEVELOPMENT OF RADIATION-DAMAGE HALOS IN LOW-QUARTZ: CATHODOLUMINESCENCE MEASUREMENT AFTER HE+ ION IMPLANTATION - Komuro K.; Horikawa Y.; Toyoda S. (My University, 2002)
In cathodoluminescence (CL) images of synthetic low-quartz samples after He+ implantation at 4 MeV with a dose density over 1.14 × 10-4 C cm-2, bright CL halos of about 14 µm in width from the implantation surface are recognized. These widths are consistent with the theoretical range. This confirms experimentally that the CL halos in low-quartz found in geological samples are formed by alpha radiation. It also shows that CL colour continuously changes with dose density, demonstrating that it is possible to use the CL halo as a new dosimeter that is useful for dating and analysis of radionuclide migration in natural geological media.